(3QSGdI aj CSeGA GddHf hCLRGFg GdJi jbY aj GdcJH hHjfgG aQhbs - (3GHf GdJdejP , gHI Gddg Hf UGYO Hf gHI Gddg Hf EHQGgje Hf Ydj, CHh GdMSf Gejf GdOhdI,J (B560 (3g` s
(3ChdgG (B:s
(3GddHf GdMdjH GdMdh CLRGFg KdKI LHfjI hRHOjI heGFjI hgj eeJRLI HGdWHY heNJda fSHJgG HGdCcKQ hGdCbd s
(3BNQgG (B:s
(3MJi jLJeY efgG TF cKjQ hgh OSe LOkG hcd HGdYSd ZPG cGf QWHkG hHGdJeQ hGdOHS hZPG jHS cGf cGdLHf ai jHSg GdG Gf WYeg ZjQ WYeg s
(3Vef eLehY , JQJjHgG (B: (3GdQSGdI GdSGOSIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B72 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B138s
(3eUOQ GbJfGA GdCUd (B:s
(3eLdS ThQGi (B(568) s
Keywords: (3GdWHs